Rabindranath Tagore and the Democratic Theory - Bagchi, Amiya Kumar (JOURNAL OF INDIAN EDUCATION, 2014)
Democracy has been regarded as the ideal of political systems for attaining human freedom. Rabindranath Tagore had written extensively on the ideal of mukti, which he insisted had a different connotation from the European liberal ideal of freedom. The latter, according to him, was an ideal centred on acquisitiveness, on the possessive individual, as the individual has been conceputalised, according to one interpretation from Hobbes to Locke. Tagore’s mukti was the ability of the individual to transcend himself, to realise that she/ he was both a part of nature and of a human society to which she/he was connected by innumerable threads of nurture, culture, sustenance and love.